The Comparative Study between Speak Pal and Fully Fluent Application toward Students’ Speaking Skill - Novi Puji Lestari; Yayu Heryatun (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
This study aims to compare two mobile applications, Speak Pal and Fully Fluent, to evaluate their benefits towards EFL learners' speaking skills. Speak Pal connects users with native speakers worldwide, offering real-time conversation practice with various accents and dialects. Meanwhile, Fully Fluent utilizes an Artificial Intelligence (AI) tutor,